2013
DOI: 10.1186/1471-2121-14-35
|View full text |Cite
|
Sign up to set email alerts
|

A simple methodology to assess endolysosomal protease activity involved in antigen processing in human primary cells

Abstract: BackgroundEndolysosomes play a key role in maintaining the homeostasis of the cell. They are made of a complex set of proteins that degrade lipids, proteins and sugars. Studies involving endolysosome contribution to cellular functions such as MHC class I and II epitope production have used recombinant endolysosomal proteins, knockout mice that lack one of the enzymes or purified organelles from human tissue. Each of these approaches has some caveats in analyzing endolysosomal enzyme functions.ResultsIn this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 30 publications
2
32
0
Order By: Relevance
“…The pH of PBMCs cell extracts was reduced to 4-5.5 in order to specifically activate cathepsins (24). Similar PI-induced alterations of cathepsin activities were observed in PBMC extracts albeit with a lower fold change (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The pH of PBMCs cell extracts was reduced to 4-5.5 in order to specifically activate cathepsins (24). Similar PI-induced alterations of cathepsin activities were observed in PBMC extracts albeit with a lower fold change (unpublished data).…”
Section: Resultsmentioning
confidence: 99%
“…In order to analyze how PI-induced changes in cathepsin activities alter antigen processing in compartments involved in cross-presentation we used our in vitro antigen degradation assay (19, 24). We previously showed that the reduction of cellular extracts pH to 4 activates cathepsins, inhibits proteasome and aminopeptidase activities and mimics degradation conditions in purified endolysosomes (19, 24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent article has demonstrated the utility of crude lysates from peripheral blood mononuclear cells (PBMCs) in characterizing endolysosomal protease activity during antigen processing (Vaithilingam et al. ).…”
Section: Introductionmentioning
confidence: 99%